ANALISIS GAYA BELAJAR VISUAL, AUDITORI, DAN KINESTETIK PESERTA DIDIK TERHADAP HASIL BELAJAR MATA PELAJARAN IPA KELAS V SDN 6 CENDONO - Irsyad Fardani; Ary Delia Maqfiroh; Ulin Nikmati Millati Askha; Putri Amelia Noviyanti (Jurnal PGSD Musi, 2023)
Science subjects need accuracy in determining learning styles, so the teacher's role is very important in improving learning outcomes, especially science subjects, because science lessons are very closely related to nature. This study aims to determine the learning styles and the impact of learning styles visually, autiotorily, and kinesthetically for students of class V to SD 6 cendono. This type of learning style has problems with what the teacher explains, often forgets to do the assignments the teacher has given orally, and is always wrong in doing what the teacher orders, and has difficulty expressing what is thought. The teacher is able to place learning styles according to the material that students have studied, so that students are able to develop the value of their learning outcomes even more, especially in science subjects. Learning style is an aspect that needs attention. Learning styles are also an easy way for students to capture, organize, and process the information they receive.